A rare case of spontaneous neonatal splenic haemorrhage - Kamaludin, Noor Khairiah; Shamsuddin Perisamy, Rajeev (UPM-MTDC, 2025)
Background: Spontaneous splenic haemorrhage in neonates is extremely rare and often fatal due to delayed diagnosis from non-specific clinical signs. Case Presentation: A term neonate presented on day two of life with pallor, tachycardia, and abdominal distension. Severe anaemia was noted. Ultrasound revealed a heterogeneous peri-splenic mass; CT confirmed a large peri-splenic hematoma and hemoperitoneum. Despite emergent splenectomy, the infant deteriorated and received palliative care. Conclusion: Neonatal splenic haemorrhage, though rare, should be considered in neonates with unexplained anaemia and abdominal distension. Early imaging is critical for diagnosis and timely intervention